• Magoosh
Study with Magoosh GMAT prep

Available with Beat the GMAT members only code

• Free Veritas GMAT Class
Experience Lesson 1 Live Free

Available with Beat the GMAT members only code

• Award-winning private GMAT tutoring
Register now and save up to \$200

Available with Beat the GMAT members only code

• Free Practice Test & Review
How would you score if you took the GMAT

Available with Beat the GMAT members only code

• 5-Day Free Trial
5-day free, full-access trial TTP Quant

Available with Beat the GMAT members only code

• Free Trial & Practice Exam
BEAT THE GMAT EXCLUSIVE

Available with Beat the GMAT members only code

• 1 Hour Free
BEAT THE GMAT EXCLUSIVE

Available with Beat the GMAT members only code

• Get 300+ Practice Questions

Available with Beat the GMAT members only code

• 5 Day FREE Trial
Study Smarter, Not Harder

Available with Beat the GMAT members only code

• Reach higher with Artificial Intelligence. Guaranteed
Now free for 30 days

Available with Beat the GMAT members only code

## From Kaplan Diag. test equation

This topic has 3 member replies
Joined
10 Dec 2006
Posted:
363 messages
Followed by:
2 members
7

#### From Kaplan Diag. test equation

Wed Mar 21, 2007 6:45 am
For the equation x^2 + 2x + m = 5, where m is a constant, 3 is one solution for x. What is the other solution?

a) -5
b) -2
c) -1
d0 3
E) 5

What do you do? do you subtiutute 3 where x is? I thought it was 5...

_________________

### Top Member

Roland2rule Legendary Member
Joined
30 Aug 2017
Posted:
713 messages
Followed by:
4 members
Fri Sep 29, 2017 2:30 pm
since 3 is one of the solutions of the quadratic equation, we will represent the whole solution with a letter say 'y'.
x=3 or x=y
and x-3=0 or x-y=0
(x-3)(x-y)=0
expanding the equation above, we have
x(x-y) - 3(x-y) = 0
x^2 - xy-3x+ 3y =0
x^2 - (y+3)x + 3y =0
Comparing this newly derived form of the equation with the original question, we observe that:
-(y+3)=2 ------------(1)
-y-3=2
-y=2+3=5
-y=5
y=-5
Hence, we obtained the other solution of the equation as required. option A is correct

Cybermusings Legendary Member
Joined
27 Mar 2007
Posted:
559 messages
Followed by:
2 members
5
Tue Mar 27, 2007 9:55 am
For the equation x^2 + 2x + m = 5, where m is a constant, 3 is one solution for x. What is the other solution?

a) -5
b) -2
c) -1
d0 3
E) 5

x^2 + 2x + m = 5

3 is one solution for x

Thus the quadratic equation has to look like

x^2 + 2x + m - 5 = 0

For 3 to be one root it has to look like this

x^2 - 3x + x + m - 5 = 0

Therefore even m - 5 = -3

Therefore m = -3 + 5 = 2

Thus x^2 - 3x + x + 2 - 5

= x ^2 - 3x + x - 3

= x(x-3) + 1(x-3)

Thus the other root of the equation is -1

I aint too good at explaining but hope this helps

Neo2000 Legendary Member
Joined
27 Jan 2007
Posted:
519 messages
31
Test Date:
30/09
Target GMAT Score:
710
Wed Mar 21, 2007 7:50 am
Yup, you substitute 3. See, a solution for X implies that X=3 will satisfy the given equation.

You get 9 +6 +m = 5
or m = -10

so you finally get x^2 +2x -10 = 5
x^2 +2x-15 = 0
(X+5)(X-3) = 0

so the solution is X = -5 or X = 3

Option A

### Best Conversation Starters

1 lheiannie07 72 topics
2 LUANDATO 60 topics
3 ardz24 48 topics
4 AAPL 46 topics
5 M7MBA 45 topics
See More Top Beat The GMAT Members...

### Most Active Experts

1 Jeff@TargetTestPrep

Target Test Prep

141 posts
2 Brent@GMATPrepNow

GMAT Prep Now Teacher

136 posts
3 GMATGuruNY

The Princeton Review Teacher

134 posts
4 Rich.C@EMPOWERgma...

EMPOWERgmat

128 posts
5 Scott@TargetTestPrep

Target Test Prep

99 posts
See More Top Beat The GMAT Experts